Dinámica de crecimiento de una plantación de Eucalyptus saligna Smith en la finca La Soledad, Parroquia Alamor, Cantón Puyango, Provincia de Loja.” - Campoverde Ramírez, Dalton Andrés (2023)
The establishment of forest plantations is an activity of great importance for the economic, social and environmental sector, because it helps to reduce the direct pressure that native forests receive from deforestation, as well as to meet the demand for wood worldwide that is used as raw material, and is part of ecological restoration contributing to improve ecosystem services. In this context, the present study contributes to the knowledge about the dynamics of growth of Eucalyptus saligna Smith at 4 years of age, in a forest plantation of 30 hectares located in the La Soledad farm, Alamor parish, Puyango canton of the province of Loja. The research determined the growth of the species in diameter (cm), height (m), basal area (m2) and volume (m3) from the measurement of dasometric variables. Likewise, a mathematical model was established for the construction of volume tables, which can be used in subsequent research. To carry out this research, sampling plots were established in the plantation and the diameter and height of the individuals were measured. A total of 1066 individuals were recorded at 48 months of age in the sampled area (1.55 hectares). With the data obtained, an analysis of variance (ANOVA) was performed to determine the growth of the dasometric variables. The results showed that the planting of Eucalyptus saligna Smith continues in the growth stage; therefore, the greatest growth and increase at 48 months of age, still does not reach the break-even point. Keywords: Analysis of variance, growth and increase, dasometric variables, forest plantations, Eucalyptus saligna.